Impact of E-Payment Platforms Among Selected Micro-Entrepreneurs in Taguig City: Determinants for Enhanced Guidelines in Collection and Disbursement Process - Kim Joshua Pueblos; Emilio Timoteo Jr (PT FORMOSA CENDEKIA GLOBAL, 2023)
The increasing use of e-payment as a mode of settling financial obligations has become more prevalent due to Covid-19 and physical distancing measures. This has been identified as a key factor in driving financial inclusion and economic growth, especially in emerging nations. However, limited research exists on the impact of e-payment platforms on micro-entrepreneurs. This study aims to investigate the impact of e-payment platforms among selected microentrepreneurs in Taguig City and to identify the determinants for enhanced guidelines for the collection and disbursement process using the e-payment system. A quantitative method of research and exploratory design with the use of a survey questionnaire was employed. The study found that an effective epayment platform is characterized by its ease of learning, control, and navigation, as well as the ability to increase the security of financial transactions. Moreover, the study revealed that e-payment platforms can help increase sales, enhance collection convenience, and simplify salary disbursements. However, the study also identified technical problems as the most common issues encountered in using e-payment platforms. This study provides valuable insights for policymakers, financial service providers, and microentrepreneurs in enhancing e-payment guidelines for the collection and disbursement process, and contributes to the literature on the impact of e-payment.